Ecological Suitability Assessment and Protection Strategies for the Upper Hanjiang River Basin Based on the Analytic Hierarchy Process - Tan, Gong; Ma, Mingjun (International Journal of Natural Resources and Environmental Studies, 2026)
Against the backdrop of accelerating socio-economic development, regional ecosystems are increasingly exposed to pressures such as air pollution, soil erosion, and water scarcity, highlighting the need for more robust ecological protection. Taking the upper Hanjiang River Basin as the study area, this study integrates the Analytic Hierarchy Process with GIS-based spatial overlay to assess ecological suitability. An indicator system comprising elevation, slope, aspect, mean annual precipitation, river-buffer conditions, vegetation distribution, and land-use type was constructed, and indicator weights were determined through expert judgment and pairwise comparison matrices that passed the consistency test. The results show that areas rated suitable or above account for approximately 70% of the study area, indicating an overall favorable level of ecological suitability. Spatially, suitability is relatively low in the Qinling and Daba mountain belts and comparatively high in the central Hanjiang valley and around urbanized areas. Localized high-suitability clusters, such as meadow valleys near the Baohe Basin, are closely associated with favorable vegetation cover and relatively stable ecological conditions, whereas strip-like low-suitability belts between the northern Daba Mountains and the Hanjiang main stem are strongly constrained by slope and aspect and should therefore be prioritized in soil-erosion control. On this basis, targeted strategies are proposed for biodiversity conservation, water-resource protection, and rational land-use planning so as to support ecological restoration, environmental governance, and sustainable development in the upper Hanjiang River Basin.